Adaptation of the Gabby conversational agent system to improve the sexual and reproductive health of young women in Lesotho - Nkabane-Nkholongo, Elizabeth; Mokgatle, Mathildah; Bickmore, Timothy; Julce, Clevanne; Jack, Brian W. (Frontiers in Digital Health, 2023)
Young women from the low-middle income country of Lesotho in southern Africa commonly report low sexual and reproductive health knowledge and engage in risky sexual behaviours. The purpose of this paper is to describe the adaptation of an evidencebased conversational agent system for use in Lesotho and provide qualitative data about the success of the adaptation.Methods: An embodied conversational agent system used to provide preconception health advice in the United States was clinically and culturally adapted for use in the rural country of Lesotho in southern Africa. Adaptations were guided by input from potential end users, health leaders and district nurses. Focus group discussions with young women aged 18-28 years who had used the newly adapted system renamed "Nthabi" for 3-4 weeks, and key informant interviews with Ministry of Health leadership were conducted to explore their views of the acceptability of the adaptation "Nthabi". Data were analysed with Nvivo software and a thematic content analysis approach was used.Results: Thirty-three women ages 18-28 years used Nthabi for 3-4 weeks; 8 (24.2%) were able to download and use the app on their mobile phones, and 25 (75.8%) used the app on a tablet lent to them. Focus group participants (n=33) reported that adaptations were culturally appropriate, and provided relevant clinical information. Participants emphasized that the physical characteristics, personal and non-verbal behaviours, use of Sesotho words and idioms, and sensitively delivered clinical content were culturally appropriate for Lesotho. Key informants of the Ministry leadership (n=10) agreed that the adaptation was successful, and that the system holds great potential to improve the delivery of health education in Lesotho. Both groups suggested modifications, such as using the local language and adapting Nthabi for use by boys and young men.Conclusions: Clinically tailored, culturally sensitive, and trustworthy content provided by Nthabi has the potential to improve accessibility of sexual and reproductive health information to young women in the low-middle income country of Lesotho.